Tanggung Jawab Pemerintah Daerah Maluku Tengah Dalam Melaksanakan Penetapan Hutan Adat - Hatuluayo, Rasyid; Pattinasarany, Yohanes; Holle, Erick Stenly (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2025)
Forests have a very important position in indigenous communities because forests are a place of residence for the community, providing a livelihood for the community. The problem of ownership of customary land rights or customary forests is one of the main causes of forestry conflicts in Indonesia. Conflicts over recognition of customary land rights holders are very detrimental to indigenous communities. Conflicts that often occur are the uncertainty of the status of customary community rights in forest areas and the unclear boundaries of forest areas. Conflicts over ownership of these rights often put indigenous communities in a weak position. Most cases of conflict in customary forest areas have not been resolved properly to date. Based on the provisions of Law No. 23 of 2013 which is the legal basis for granting authority to the government in determining customary law communities to customary forests through regional regulations, the regional government, more precisely the Central Maluku regional government, has not carried out its responsibilities in terms of determining customary forests, because until now the Central Maluku regional government has not ratified regional regulations regarding the determination of customary law communities, the requirement for determining customary forests is customary law communities, and this recognition is stated in regional regulations which are the responsibility of the regional government.